PERAN PEMBIMBING KEMASYARAKATAN DALAM LAYANAN BIMBINGAN INDIVIDU TERHADAP REINTEGRASI SOSIAL KLIEN DI BAPAS KELAS I BANDAR LAMPUNG - tanjung, Noffiyanti (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2026)
Drug abuse often results in a range of social challenges following the completion of legal proceedings, including low self-esteem, difficulties in social adaptation, limited independence, and persistent stigma from both family and society. These challenges may hinder the process of social reintegration if not supported by appropriate and structured guidance. The Class I Correctional Center (Bapas) in Bandar Lampung plays a crucial role in delivering individual guidance services aimed at assisting clients in improving their behavior and preparing for successful reintegration into society. This study seeks to examine the implementation of individual guidance in enhancing the social reintegration of clients involved in drug abuse cases. This study employed a qualitative approach using a descriptive field research design. The participants consisted of six informants selected through purposive sampling, including five clients and one correctional counselor. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the implementation of individual guidance follows several systematic stages, including problem identification, goal setting, planning, implementation, as well as evaluation and follow-up. The guidance process contributes positively to clients’ development, particularly in improving self-control, strengthening responsibility, enhancing social adaptability, and rebuilding social relationships. These outcomes are supported by an empathetic and sustained counseling approach, as well as strong institutional support. In conclusion, individual guidance plays a significant role in facilitating the social reintegration of clients.